A Geographic Knowledge Base for Semantic Web Applications - Chaves, Marcirio (2012)
This paper introduces GKB, a repository based on a domain independent meta-model for integrating geographic knowledge collected from multiple sources. We present the architecture, the repository design and the data cleaning and knowledge integration processes. We also describe the rules developed to add new knowledge to GKB. GKB includes tools for generating ontologies, which are being used by multiple semantic web applications. To illustrate how it is being used, we present some of the applications that interact with the repository or load ontologies created with GKB.